AB0021 A genome-wide snp linkage analysis suggests a novel susceptibility gene for ankylosing spondylitis. (12th June 2018) - Lin, Z.; Gui, L.; Zhang, Y.; Lv, Q.; Qi, J.; Fang, L.; Zhang, X.; Gu, J.
Abstract : Background: Ankylosing Spondylitis (AS) is a chronic, progressive and inflammatory disease, which is considered to be hereditary. However, the responsible molecular genetic determinants remain unidentified. Objectives: To detect susceptibility gene(s) for AS by using an affected-only linkage analysis and high density single nucleotide polymorphism (SNP) in genome-wide manner. Methods: All AS patients in three families of Cantonese were recruited. Their clinical material were collected by questionnaires. Genomic DNA derived from individual peripheral blood leukocytes was genotyped using Illumina HuamHap 610-Quad SNP Chip. Genotype data were generated using the Illumina BeadStudio 3.2 software. An affected-only linkage analysis was carried out using non-parametric and parametric linkage analysis. The customised allele frequencies were based on the 980 Cantonese healthy controls. SNP genetic map positions were interpolated as their physical positions in megabyte. Results: 1. Clinical data: The mean age was 42.3±14.9 years (ranging from 18 62 years), mean age of onset was 23.8±7.4 years (ranging from 10 30 years), mean duration of affection was 17.0±13.0 years (ranging from 0.2 50.0 years), and the sex ratio of male to female was 2.5: 1. There was no Iritis and dactylitis, hip involvement (4, 19.05%), peripheral arthritis (4, 19.05%), inflammatory back pain (21, 100%) and HLA-B27 positive (20, 95.24%). 2. Results of non-parameter linkage analysis: The highest LOD value was found in chromosome 16, which reached 2.362. Although chromosome 6 was considered to be relative to the pathogenesis of AS, its LOD value was 1.499 and the range of the peak was located in 6 p21, where 96 SNPs (such as rs6930977) were included. 3. Results of parameter linkage analysis: The LOD value of chromosome 16 was 4.6807 and higher than that of other chromosomes which were less than 3 by the same analysis. A susceptibility locus was found in 16q12, spanning 88.5 Kb with LOD value above 3 (ranging: 51030764 51915940). 4. Susceptibility genes: According to the result of parameter linkage analysis in chromosome 16, seven genes (TOX high mobility group box family member 3 (TOX3), LOC643714, LOC146253, LOC100132440, LOC390730, LOC100128523 and chromodomain helicase DNA binding protein 9 (CHD9)) could be detected in the position where the LOD value exceeded 3. Interestingly, six SNPs could be found in CHD9 gene. Likewise, they were also found in another association analysis, which included 400 AS patients and 977 healthy controls. P value for SNP rs10153130 was 0.005879 (adjust p≤0.05/6=0.00833). Conclusions: Genome-wide SNP linkage analysis in three AS families supports that a susceptibility locus for AS was found in 16q12, spanning 88.5 Kb with LOD value above 3 (ranging: 51030764 51915940). Acknowledgements: This study was supported by Guangdong Natural Science Funds for Distinguished Young Scholar (Grant No. 2014A030306039), High-level personnel of special support program for Technology Innovative Talents and the Top Young of Guangdong Province (Grant No. 2015TQ01R516), Distinguished Young Scholar Candidates Programme for The Third Affiliated Hospital of Sun Yat-Sen University and Pearl River Nova Program of Guangzhou (Grant No. 201610010005). Disclosure of Interest: None declared